2017
DOI: 10.1158/1078-0432.ccr-16-1297
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Study Testing a New Radioenhancer Using Nanoparticles (NBTXR3) Activated by Radiation Therapy in Patients with Locally Advanced Soft Tissue Sarcomas

Abstract: This phase I study aimed to determine the recommended dose (RD), safety profile, and feasibility of a procedure combining intratumoral injection of hafnium oxide nanoparticles (NBTXR3; a radioenhancer) and external beam radiotherapy (EBRT) for preoperative treatment of adults with locally advanced soft tissue sarcoma (STS). Patients had a preoperative indication of EBRT for STS of the extremity or trunk. Baseline tumor volume (TV) was calculated by MRI. NBTXR3 was injected percutaneously into tumors at 53.3 g/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 29 publications
2
161
0
Order By: Relevance
“…NBTXR3/Hensify is a 50 nm crystalline hafnium oxide nanoparticle with negatively charged phosphate coating, developed and marketed by Nanobiotix . NBTXR3/Hensify enhances external radiotherapy via a physical mode of action that relies on hafnium's natural radioenhancing properties . Specifically, the interaction between ionizing radiation and hafnium facilitates a higher energy deposit as compared to ionizing radiation without hafnium interaction; this results in the generation of significantly more electrons and increases radiation‐mediated cell death from standard radiation oncology procedures .…”
Section: New Approvalsmentioning
confidence: 99%
“…NBTXR3/Hensify is a 50 nm crystalline hafnium oxide nanoparticle with negatively charged phosphate coating, developed and marketed by Nanobiotix . NBTXR3/Hensify enhances external radiotherapy via a physical mode of action that relies on hafnium's natural radioenhancing properties . Specifically, the interaction between ionizing radiation and hafnium facilitates a higher energy deposit as compared to ionizing radiation without hafnium interaction; this results in the generation of significantly more electrons and increases radiation‐mediated cell death from standard radiation oncology procedures .…”
Section: New Approvalsmentioning
confidence: 99%
“…In another study, it was shown that NBTXR3, a 50 nm hafnium oxide nanosphere, can substantially enhance radiation therapy efficacy when intratumourally injected into different tumour xenograft models 76 . This nanoparticle formula is in phase II/III clinical trials for improving radiation therapy against advanced soft tissue sarcoma of the extremities 77 , and in phase I/II for head and neck cancer, liver cancers (both hepatocellular carcinoma and liver metastases), prostate cancer and rectal cancer radiation therapy. Recently, AGuIX, a ~3 nm polysiloxane and a Gd-DTPA conjugate, was investigated as a nanoparticle radiosensitizer 14 .…”
Section: Key Concepts and The Status Quomentioning
confidence: 99%
“…More importantly, Hf is a high Z atom ( Z = 72), which enables it to be used as radiosensitive agent . HfO 2 nanoparticles can serve as a radiosensitizer by physical mechanism . When HfO 2 enters the tumor tissues and is activated by external radiation beam, it can emit high energy electrons and increase the electron density deposited within irradiated tissues, resulting that the dose of X‐ray delivered to the tumor is magnified while the dose passing through healthy tissues remains unchanged.…”
Section: The Clinical Translation Of Nanomaterial‐mediated Tumor Radimentioning
confidence: 99%